Funciones desempeñadas en el Banco de Crédito del Perú - BCP periodo (2011-2017) - Alcántara Pretel, Juan Enrique (2019)
The present work of professional proficiency titled: "Functions performed in the Banco de Credito del Peru - BCP period (2011 - 2017)", has as general objective to analyze and describe the professional experience obtained in the Banco de Credito del Peru in the period 2011 to 2017, in order to announce the importance of the position and the roles played in as an SME banking executive. The document is structured in four chapters, the first describes the institutional context of Banco de Credito del Peru within the Peruvian financial system and then moves to the micro sector consisting of multiple banks, as well as the functions commissioned and performed according to the Organization and Functions Manual (MOF). Likewise, in this first chapter the problems found in the workplace and the objectives of the report were identified; both general and specific, using observation and documentary analysis as study methodology. In the second chapter we present the scientific and technical basis of work performance obtained in Banco de Credito del Peru. In the theoretical framework, information was collected on similar problems, contributions and solutions. The third chapter describes the strategies for solving the problems identified in previous chapters, so that in the fourth chapter the critical assessment is detailed based on the experience and training received in the professional academic school of Administration of the National University of Trujillo. Finally, based on the results obtained, the conclusions are detailed, being one of the most important the need to intensify courses of negotiation techniques and credit risk management in the School of Administration of the National University of Trujillo. In this situation, the contribution was to reflect a critical appreciation of the professional training of the Administration career based on my work experience, to be able to perform efficiently and competitively.